Parodi Pada Iklan Televisi Axis Serial Iritology Melalui Pendekatan Format, Struktur, Gaya Dan Teknik Iklan - Gita, Intan Swasti; Rosmiati, Ana Ana (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
Axis advertisement is an advertisement that uses a parody approach using cultural references and community habits, one of which is the Axis Serial Iritology advertisement. The issue in this study is about parody on Axis Serial Iritology television advertisement through format, structure, style, and advertising techniques with the aim of describing parody on Axis Serial Iritology television advertisements through advertising approach. The research method used is descriptive qualitative to analyze this advertisement based on the format, structure, style, and technique of advertising according to Vilanilam and Varghese. Advertising approach using problem-solution format, a slice of life, burlesque, and testimonial format is used in the Axis serial Iritology ad. The advertising structures used are vignette, comparison, and continue series, whereas the ad style used is dominantly comedy, however, there are some scenes that are inserted in fantasy style. The technique used in the Axis Iritology advertisement uses the touch of animation and special effects in the middle and end of the ad. Parody in advertisements can be the main attraction in presenting an ad.